Dissipativity of positive switched systems using multiple linear supply rates. (May 2019) - Wang, Peng; Zhao, Jun
Abstract: In this paper, we are devoted to investigating dissipativity for a class of positive switched systems by exploiting multiple linear copositive storage functions and multiple linear supply rates. A novel concept of dissipativity is presented, which depicts the overall dissipativity property of positive switched systems without the requirement of the classic dissipativity property of each positive subsystem. A sufficient condition ensuring dissipativity for positive switched systems is given under a designed switching signal. Meanwhile, L 1 gain and stability are also get based on dissipativity. Dissipativity and positivity are shown to be maintained under positive feedback interconnection, and a small-gain property is also given. All presented conditions are formulated as a linear programming problem. Two examples are provided to illustrate the effectiveness of the main results.